Sequence Determinants of Quaternary Structure in Lumazine Synthase - Fornasari, Maria Silvina (2004)
Riboflavin, an essential cofactor for all organisms, is biosynthesized in plants, fungi and microorganisms. The penultimate step in the pathway is catalyzed by the enzyme lumazine synthase. One of the most distinctive characteristics of this enzyme is that it is found in different species in two different quaternary structures, pentameric and icosahedral, built from practically the same structural monomeric unit. In fact, the icosahedral structure is best described as a capsid of twelve pentamers. Despite this noticeable difference, the active sites are virtually identical in all structurally studied members. Furthermore, the main regions involved in the catalysis are located at the interface between adjacent subunits in the pentamer. Thus, the two quaternary forms of the enzyme must meet similar structural requirements to achieve their function, but, at the same time, they should differ in the sequence traits responsible for the different quaternary structures observed. Here, we present a combined analysis that includes sequence-structure and evolutionary studies to find the sequence determinants of the different quaternary assemblies of this enzyme. A data set containing 86 sequences of the lumazine synthase family was recovered by sequence similarity searches. Seven of them had resolved three-dimensional structures. A subsequent phylogenetic reconstruction by maximum parsimony (MP) allowed division of the total set into two clusters in accord with their quaternary structure. The comparison between the patterns of three-dimensional contacts derived from the known three-dimensional structures and variation in sequence conservation revealed a significant shift in structural constraints of certain positions. Also, to explore the changes in functional constraints between the two groups, site-specific evolutionary rate shifts were analyzed. We found that the positions involved in icosahedral contacts suffer a larger increase in constraints than the rest. We found eight sequence sites that would be the most important icosahedral sequence determinants. We discuss our results and compare them with previous work. These findings should contribute to refinement of the current structural data, to the design of assays that explore the role of these positions, to the structural characterization of new sequences, and to initiation of a study of the underlying evolutionary mechanisms.